(untitled) (Eurasian Journal of Ecology, 2021)
This paper evaluates the results of hydrophysical and hydrochemical indicators of Lake Akbas of the Kokshetau State National Natural Park, which belongs to the category of specially protected natural areas. Changes in the lake area over a period of about 50 years are shown. In terms of water color and turbidity, there has been a decrease over the past 3 years. The area of the Akbas lake basin has decreased by 15.3% over the past 50 years. During the study period, the content of dry waste in the lake water exceeded the MAC by 1.1–1.5 times annually. Lake Akbas is moderately polluted in 2018-2019 in terms of the level and quality of class III pollution. However, it was found that some hydrochemical parameters exceed the MAC. Along with the hydrophysical and hydrochemical indicators of Lake Akbas, we identified the species composition of microalgae in the lake, seasonal changes and conducted a systematic analysis. As a result of the study, the algae flora of Lake Akbas consisted of 61 species, 20 of which are indicator-saprobic microalgae. To study the sensitivity of algae to environmental factors and various chemical reactions, we carried out biotesting of water samples from Lake Akbas. Biotesting showed that the Chlorella sp-3K strain is moderately sensitive to toxic concentrations in Lake Akbas. Researches have shown that bioassays for microalgae in lake water are quick and easy and complement the results of chemical studies. According to the results of hydrophysical, hydrochemical studies and biotesting of algocenoses, it was determined that the water of Lake Akbas belongs to 3 classes of pollution. Key words: Нydrophysical and hydrochemical indicators, algoflora, biotesting.